Development of Cultural Arts Learning Media from Corn Husk Waste Materials for Students with Special Needs - Hasdiana, Hasdiana; Dangkua, Suleman (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Extraordinary School is a formal educational institution that provides education specifically for children with special needs. One of the subjects taught at Public Extraordinary School Gorontalo is art and culture. There are difficulties experienced by teachers in the art and culture subject for students at Extraordinary School because so far there has been no special media used to teach the art and culture subject, where subject teachers must present material with different student disabilities. This study intends to determine the potential of corn husk fiber as a learning medium for children with special needs at Public Extraordinary School Gorontalo. The method used in this study is the creation method. The creation process consists of several stages, namely stage exploration, stage improvisation, and stage formation. The results of this basic research indicate that there are new findings in the form of a formulation of the concept of a trial of making and using corn husks as one of the raw materials that are the basic materials for making learning media in the form of teaching aids equipped with Braille letters and can be used as an aid in the teaching and learning process in the art and culture subject, visual arts material, and the main topic of decorative variety for blind students at Public Extraordinary School Gorontalo.